Teaching a Large Course On Contemporary Fiction - Ohmann, Richard (Radical Teacher, 2022)
My intention was, not to survey political novels, or the ones I like best, or novels that meet some ahistorical standard of excellence, but to consider those that are in one way or another central to American bourgeois culture, and to help students understand that culture through their reading of the novels. . . . I adopted an approach that might be unsympathetically described as building the novels up in order to knock them down. But I think the strategy is warranted. Looking closely at what's good in one of these novels almost invariably means following some insight into the difficulty of living a good life on the terms offered by our society. (Many of the novelists would probably let it go at "living a good life," but since they take America as a given, the mimesis of capitalism is always there.) This is, to put it crudely, the problem posed by each novel, often revealingly. Most go on to hint at solutions, and here's where I think they fall apart. They displace politics and offer personal or anarchist or pre-industrial remedies for human sorrows that are rooted in advanced capitalist, industrial society.